Stochastic optimal control problem with delay - Agayeva, Ch.A. (Інститут математики НАН України, 2006)
A stochastic optimal control problem with variable delay on phase and on control is
considered. The maximum principle for a nonlinear stochastic control system with
controlled diffussion coeffcient is proved.